2019
DOI: 10.1016/j.cegh.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Path to severe acute malnutrition in children below 2 years of age: Findings of qualitative research in Uttar Pradesh, North India

Abstract: Introduction: Malnutrition in infancy contributes to high mortality and morbidity. In India, government has established nutrition rehabilitation centres for managing children with severe acute malnutrition. The study was conducted with aim to understand how community perceived malnutrition and how child's size at birth, infant and young child feeding related behaviours and child's illness were associated with decline in the child's growth or health. Methods: Qualitative research employing focused ethnographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
3
13
0
2
Order By: Relevance
“…Many mothers, for example, reported being angry with how they are talked to or their children are handled in health facilities and that they therefore avoid those facilities, distrust or ignore the advice given, or leave as soon as possible. These findings resonate with those from other low resourced contexts: concerns about poor inter-personal handling and health workers' negative attitudes are widespread in the literature [10,11,33]. The critical importance in service delivery of recognising and responding to the communication and emotional needs of patients and their family members is therefore highlighted; dimensions of good quality of care are often under-supported in health worker training [33].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Many mothers, for example, reported being angry with how they are talked to or their children are handled in health facilities and that they therefore avoid those facilities, distrust or ignore the advice given, or leave as soon as possible. These findings resonate with those from other low resourced contexts: concerns about poor inter-personal handling and health workers' negative attitudes are widespread in the literature [10,11,33]. The critical importance in service delivery of recognising and responding to the communication and emotional needs of patients and their family members is therefore highlighted; dimensions of good quality of care are often under-supported in health worker training [33].…”
Section: Discussionsupporting
confidence: 61%
“…Social relationships within and beyond the home, and availability and access to support from family and community-based organisations can also play an important role in treatmentseeking decisions, including in providing advice, accessing necessary funds, or supporting parents with childcare and other tasks [9]. At the health service or system level, influences on treatment-seeking pathways include how far away different types of services are located, their costs, and the perceived quality for the symptoms observed [10][11][12]. All of these influences are in turn shaped by structural drivers such as access to employment and availability of essential services.…”
Section: Introductionmentioning
confidence: 99%
“…The social customs of discarding colostrum and giving prelacteal feeds still acted as a hindrance for colostrum feeding. Similar observations were made by Awasthia (2019) 19 in their study in Uttar Pradesh who found that pre-lacteal feeding was a major barrier to exclusive breastfeeding.…”
Section: Colostrum Feeding and Exclusive Breastfeedingsupporting
confidence: 86%
“…2,3 Socio-economic inequalities remain major barriers in achieving Sustainable Development Goals (SDGs) in recognition of the challenges in nutrition, health, and hygiene/sanitation in India. 4 Previous studies have identified that various factors such as social identity, mother's education, and poverty affect child's health and growth development among those who belong to marginalized and disadvantaged communities. 5,6 However, very few studies have focused on child health and nutrition development with geographical factors and regional diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Uttar Pradesh is one of the top three states in India and has the highest child mortality and morbidity rates in the country. 4,10,22,19 The state is facing severe under-nutrition among women and children. 19,23 Poor socio-economic development, low women's education and empowerment are major contributors to high child malnutrition in the state.…”
Section: Introductionmentioning
confidence: 99%